IoT-Based Soil Monitoring System with Agricultural Drone - Abang Mustapha, Dayang Umira Athira Fatini (IRC, 2020)
The purpose of this study is to discover the mechanism with agricultural drone to sustain the environment by monitoring thru the dashboard that consists of soil performance and the deposition quantity of spraying chemical substances. The deficient method of spraying fertilizes on crops that may causes health problems and environmental pollutants due to excessive use of chemicals. Thus, agricultural drone stands to benefit substantially with regard to time saving, money value and most importantly, reducing environmental damage. Additionally, the method to gather the chemical data and specific ions in the soil is by using Electro-Chemical sensors. Hence, the data is transmitted by MQTT and the farmers are able to view the information from the monitoring dashboard. It is hoped this study will enlighten the farmers about the importance of sustainable environment and able to produce crops that are good quality in a big quantity.